Inspiring journey of a farm woman in natural farming - Bordoloi, L. J.; C. S., Karibasappa; Kumar, Sunil; Mohanty, A. K.; Kalita, H. (Indian Farming, 2025)
In the remote village of Tsongpong, Nagaland, Smt Gloria Sangtam transformed her agricultural practices through natural farming, guided by KVK Kiphire. Initially reliant on traditional methods with limited income, Smt. Gloria adopted sustainable practices such as using organic inputs and crop rotation. With training in techniques like Jeevamrut preparation and vermicomposting, she improved soil health, achieving a 49.17% increase in maize yield and raising her annual income from ` 30,000 to 1.97 lakh. As a community leader, Smt Gloria inspires fellow farmers to adopt natural farming, fostering a movement towards sustainable agriculture in Kiphire district and enhancing local livelihoods and resilience.